PENGARUH MODEL PELATIHAN PEMBELAJARAN BERBASIS KERJA TERHADAP KREATIVITAS PESERTA PELATIHAN BLK BOJONEGORO - Ristanto Ristanto; Rusijono Rusijono; Fajar Arianto (Akademika : Jurnal Teknologi Pendidikan, 2022)
The importance of human resources is based on the fact that human resources are the basic elements of every company. Human resources can determine the advantages of a company because human resources are goal makers, innovation, communication, creativity, and strategy for the company. The purpose of this study was to determine the effect of the Work Based Learning training model on the creativity of trainees at BLK Bojonegoro. This research is a qualitative research which can specifically be categorized as a qualitative research program evaluation. The sample in this study amounted to 100 trainees at BLK Bojonegoro. The results showed that the high scale of creativity (85.5%), the tasks of the training participants (83.4%), support for learning (78.8%) and clear goals (76%). In training models where exposure to real-world constraints, opportunities, policies and regulations is mandatory, work-based learning occupies an important niche in participants' experiences.